Neutrophil extracellular traps in autoimmune diseases: Analysis of the knowledge map - Wang, Wei; Su, Jing; Kang, Wenjuan; Yan, Meiqin; Pan, Jie; Zhang, Xianhui (Frontiers in Immunology, 2023)
Objective: This study aimed to provide a bibliometrics review of the knowledge structure and research hotspots of neutrophil extracellular traps (NETs) in autoimmune diseases (AIDS). Methods: Articles relevant to NETs in AIDs from 2010 to 2022 were retrieved through the Web of Science Core Collection (WoSCC) database. This bibliometric analysis was performed by VOSview, CiteSpace, and Scimago Graphica. Results: A total of 267 papers analyzed in this research were from 512 organizations in 47 countries by 1446 authors. They were published in 130 journals and cited 18,175 citations from 2,357 journals. The number of annual publications in this field is growing steadily and rapidly, with the United States, China and Germany leading the research effort. Frontiers in Immunology and Journal of Immunology have significantly impacted research in this field. Kaplan, Mariana J, from the National Institutes of Health (The United States), has the most published articles, and Brinkmann, v, from Max Planck Institute for Infection Biology (Germany), is the most co-cited author. Systemic lupus erythematosus and rheumatoid arthritis are the leading topics in this field. The trend of clinical application in the future is the development of new therapies by controlling NETs in the progression of AIDs. Conclusions: Our study summarized the research trends and developments of NETs in AIDs in recent years and would provide a reference for scholars in this field.